The complete mitochondrial genome of the freshwater crab Neilupotamon xinganense (Decapoda: Brachyura: Potamoidea) - Tan, Qi-Hong (Mitochondrial DNA B Resour, 2020)
In this study, we first obtained the complete mitochondrial genome of Neilupotamon xinganense (Decapoda: Brachyura: Potamoidea). The genome is 16,965 bp in length and typically consists of 37 genes (13 protein-coding genes, 22 tRNAs genes, two rRNAs genes, and one putative control region). In addition, the mitogenome has 20 non-coding regions ranging from 1 to 683 bp in length. This study provides DNA data for further researches on population genetics and phylogenetics.